PENGGUNAAN EWALLET DALAM MEMBENTUK PERILAKU KONSUMTIF MAHASISWA FAKULTAS EKONOMI PRODI MANAJEMEN UNIVERSITAS ISLAM BATIK SURAKARTA YANG DI MEDIASI KONTROL DIRI - Ningrum, Injati Aprilia; Maryam, Siti; Hartono, Sri (JURNAL ILMIAH EDUNOMIKA, 2024)
The aim of this research is to determine the influence of e-wallet use mediated by self-control on the consumptive behavior of students in the economics faculty of the management study program at Batik Islamic University, Surakarta. The author uses descriptive quantitative methods. Data collection using a quantitative approach uses questionnaire research instruments, statistical data analysis with the aim of testing predetermined hypotheses. The population in this study were all active students of the management study program at Batik Islamic University, Surakarta, totaling 283 students, obtained from BAAK (Academic and Student Administration Bureau). The number of samples used was 55 students. The sampling technique is purposive sampling. Researchers used multiple linear regression analysis. The results of this research show the influence of e-wallet use on consumer behavior. There is an influence of self-control on consumer behavior. There is an influence of e-wallet use mediated by self-control on the consumptive behavior of students in the economics faculty of the management study program at Batik Islamic University, Surakarta. Keywords: E-Wallet Use, Self-Control, Consumptive Behavior.